Mobile gaming in education: a bibliometric analysis of trends and performance - Pek, Lim Seong; Yob, Fatin Syamilah Che; Mee, Rita Wong Mee; Wider, Walton; Miftah, M. Zaini; Camara, Jun S. (Institute of Advanced Engineering and Science, 2025)
This bibliometric analysis, based on data from the Web of Science (WoS) database, examines the increasing role of mobile gaming in education. Mobile gaming has demonstrated strong potential to improve student engagement, motivation, and cognitive skills, yet research on its integration within formal educational settings is still emerging. By analyzing data from 247 scholarly articles published between 2014 and 2023, this study identifies key trends, influential contributors, and areas of growing interest within this field. The findings reveal a significant rise in publications and citations, underscoring the expanding recognition of mobile gaming’s educational value. Prominent themes in the literature include gamification strategies that encourage collaboration, problem-solving, and critical thinking, focusing on multiplayer online battle arenas (MOBAs) and other interactive gaming environments that facilitate active learning. The analysis also highlights leading countries, with the United States at the forefront of research output, alongside significant institutional contributions globally. These insights guide educators and policymakers on leveraging mobile gaming in educational practices while addressing potential challenges. By emphasizing the alignment of mobile gaming with sustainable development goal 4 (quality education), this study establishes a foundation for future research into innovative, technology-enhanced learning solutions that are accessible, engaging, and effective.